Detection of tumor‐derived cell‐free DNA from colorectal cancer peritoneal metastases in plasma and peritoneal fluid. (26th February 2021) - van't Erve, Iris; Rovers, Koen P; Constantinides, Alexander; Bolhuis, Karen; Wassenaar, Emma CE; Lurvink, Robin J; Huysentruyt, Clément J; Snaebjornsson, Petur; Boerma, Djamila; van den Broek, Daan; Buffart, Tineke E; Lahaye, Max J; et al.
Abstract: Tumor‐derived cell‐free DNA (cfDNA) is an emerging biomarker for guiding the personalized treatment of patients with metastatic colorectal cancer (CRC). While patients with CRC liver metastases (CRC‐LM) have relatively high levels of plasma cfDNA, little is known about patients with CRC peritoneal metastases (CRC‐PM). This study evaluated the presence of tumor‐derived cfDNA in plasma and peritoneal fluid (i.e. ascites or peritoneal washing) in 20 patients with isolated CRC‐PM and in the plasma of 100 patients with isolated CRC‐LM. Among tumor tissue KRAS/BRAF mutation carriers, tumor‐derived cfDNA was detected by droplet digital polymerase chain reaction (ddPCR) in plasma of 93% of CRC‐LM and 20% of CRC‐PM patients and in peritoneal fluid in all CRC‐PM patients. Mutant allele fraction (MAF) and mutant copies per ml (MTc/ml) were lower in CRC‐PM plasma than in CRC‐LM plasma (median MAF = 0.28 versus 18.9%, p < 0.0001; median MTc/ml = 21 versus 1, 758, p < 0.0001). Within patients with CRC‐PM, higher cfDNA levels were observed in peritoneal fluid than in plasma (median MAF = 16.4 versus 0.28%, p = 0.0019; median MTc/ml = 305 versus 21, p = 0.0034). These data imply that tumor‐derived cfDNA in plasma is a poor biomarker to monitor CRC‐PM. Instead, cfDNA detection in peritoneal fluid may offer an alternative to guide CRC‐PM treatment decisions.